US voluntary advanced teacher certification: towards the Dakar notion of EFA. Issue 5 (20th October 2019) - Rhoades, Jesse Lee; Mays Woods, Amelia; Fitzgerald, John; Trendowski, Thomas N.; Ellison, Douglas
ABSTRACT: In the year 2000, the World Education Forum developed the Dakar Framework, outlining strategies for the achievement of universal education. Among these strategies was to 'Enhance the status, morale, and professionalism of teachers.' Further, the 2014 Education for All (EFA) report indicated the necessity of 'investing in teachers.' The National Board for Professional Teaching Standards, a US-developed program, seems to meet these expectations through voluntary advanced certification. Policymakers later established completion incentives for National Board Certification (NBC). The purpose of this study was to describe National Board Certified Teachers and determine critical incentives for completion of NBC. Regression analysis indicated salary incentives are predictive of completion, explaining 20% of the variance. Overall, these results indicated that salary incentives have potential to be a compelling extrinsic incentive for voluntary professional development programs. Further, these findings suggest that similar programs within other nation-states may have comparable success through these incentive types.